A contribuição da logística reversa na gestão de resíduos sólidos: uma análise dos canais reversos de microcomputadores - Santos, Ezequiel Ferreira dos (2010)
The aim of this study is to analyze the activities of reverse logistics in solid waste management among business users of computers who are responding to the laws at the municipal, state and federal that deal with Brazil on the proper disposal of post-consumer products. This research began to be developed with the method of exploratory, seeking a better understanding of reverse logistics issues related to solid waste management sector and the profile of personal computers, through the research literature and documents. To understand the solid waste management in the logistics chain of computers, quantitative research was conducted through questionnaires to companies that use computers and perform the replacement and expansion on a regular basis. Sought, through this study, we examine the practice of reverse logistics and management of solid waste from business users of computers. It was found that the integrated management of solid waste from post-consumer PCs will be controlled by the newly enacted National Policy on Solid Waste, not yet regulated, and by other state and local laws. In the analysis of this research, we tried to check the practice of reverse logistics for post-consumer PCs in the views of various levels of solid waste management, analyzing the consumption reduction, reuse, retirement, recycling and landfilling. In this research, it was found that use of new technologies such as virtualization, resulting in a lower rate of replacement equipment. The results show that organizations do not properly receive the information necessary to suit the laws and regulations that deal with the final disposition and no guidance on how to participate in the reverse logistics programs. These factors contribute to spread disbelief that the inspections could prevent the improper disposal of computers. With respect to reuse, it was found that organizations have a tendency to reuse components and equipment internally and to make technological upgrades (upgrade), but there is some difficulty in promoting an external reuse. Regarding recycling, it was shown that the recyclers in Brazil only use a portion of the existing materials of the sets of computers and the recycling of electronic boards, which require more complex, are forwarded to the companies abroad. With respect to reverse logistics, the survey results show that the reverse channel to the final destination of PCs are better structured in medium and large.